2017
DOI: 10.1007/s41887-017-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Domestic Homicide and Serious Violence in Leicestershire with Intelligence Records of Suicidal Ideation or Self-Harm Warnings: a Retrospective Analysis

Abstract: Research Question Does prior information retained in police intelligence records about an offender's suicidal tendencies help to predict a future domestic homicide or attempted homicide? Data Records on 158,379 arrestees in 1997-2015 were examined for suicidal or selfharm warnings by date of entry and compared to 620 offenders identified in cases of domestic homicides or serious violence over the same time period. Methods The percentage of offenders in domestic homicide and serious violence cases who were know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 3 publications
0
10
0
4
Order By: Relevance
“…Oram, Trevillion, Khalifeh, Feder, and Howard’s () review found that psychiatric disorders (depression, generalised anxiety disorder and panic disorder) were associated with high prevalence and increased odds of having ever been physically violent against a partner. Button, Angel, and Sherman () analysed data from Leicestershire's police and found that it was five times more likely that offenders charged with domestic homicide had prior suicidal warning markers than did all other offenders. The relationship between mental health disorders and a history of perpetrating DVA clearly warrants further exploration but this study suggests that it may be an indicator of high risk of perpetration of domestic homicide.…”
Section: Discussionmentioning
confidence: 99%
“…Oram, Trevillion, Khalifeh, Feder, and Howard’s () review found that psychiatric disorders (depression, generalised anxiety disorder and panic disorder) were associated with high prevalence and increased odds of having ever been physically violent against a partner. Button, Angel, and Sherman () analysed data from Leicestershire's police and found that it was five times more likely that offenders charged with domestic homicide had prior suicidal warning markers than did all other offenders. The relationship between mental health disorders and a history of perpetrating DVA clearly warrants further exploration but this study suggests that it may be an indicator of high risk of perpetration of domestic homicide.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 80 domestic homicides in Leicestershire over 1997, Button et al, (2017 found that 9% of them had a suicide or self-harm marker in the Crime and Intelligence System (CIS), which has since been closed. Extrapolating from the present study's findings, approximately 77% of the Leicestershire homicide offenders who had had suicidal tendencies were unknown by the police to have suffered that problem prior to committing a homicide as Button et al, (2017) defined the crime (including attempts). Thus, the case for police investing in resources to identify more cases of overlap between suicidal tendencies and domestic abuse seems to be great.…”
Section: Discussionmentioning
confidence: 99%
“…Estudiando la intención primaria del agresor en los supuestos de H-S, los homicidas de mayor edad pre-sentan procesos más próximos a la ideación suicida que a la homicida (Salari y Sillito, 2016). Hallazgos recientes en el Reino Unido apoyan la importancia de la ideación suicida y de los intentos autolíticos en los homicidios domésticos, concluyendo que aumentan la probabilidad de los homicidios entre 3 y 5 veces, así como que los marcadores de los sistemas de inteligencia de la policía para el suicidio o la automutilación pueden proporcionar información valiosa para construir modelos de predicción más precisos para los homicidios domésticos y las agresiones graves (Button, Angel y Sherman, 2017).…”
Section: Homicidio Diádico: Homicidio Seguido De Suicidio (H-s)unclassified